Implementasi Pengelolaan Sampah di Kelurahan Oesapa Ditinjau dari Peraturan Daerah Kota Kupang Nomor 4 Tahun 2011 Tentang Penyelenggaraan Pengurangan Sampah Rumah Tangga dan Sampah Sejenis Rumah Tangga - Apris Alexandro Bansele; Jhonanis G Tuba Helan; Detji K.E.R. Nuban (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this research is to analyze the implementation of waste management in Oesapa Village in terms of Kupang City Regional Regulation No. 4/2011 on the implementation of reducing household waste and similar household waste. This research is an empirical juridical research where this research was conducted in Oesapa Village, Kelapa Lima Sub-district, Kupang City. This research uses interview guidelines for fifteen resource persons. The data was analyzed descriptively-qualitatively. Based on the results of the study that the reduction of household waste and similar household waste requires legal certainty, clarity of authority and responsibility of the government, as well as the participation of the community and business actors, so that the implementation of waste reduction can bring economic benefits, healthy for the community, and can change people's behavior that operationally, Article 9 of Law No. 18 of 2008 concerning Waste Management gives the authority to implement waste reduction to the Kupang City Government, especially Kelapa Lima District The implementation of reducing household waste and similar household waste in Kupang City is not in accordance with the methods and techniques for implementing environmentally sound waste reduction, resulting in negative impacts on public health and the environment.